(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
The removal and transportation of hydrophobic and hydrophilic nature of organic pollutants in surface water is a major factor for adsorption. Hydrophobic and hydrophilic nature of organics was measured by octanol-water partition coefficients (KOW) by shake flask method and specific UV absorbance (SUVA). This study was done in water samples of river Kali and river Krishni in Uttar Pradesh, India. River Kali and Krishni are the tributaries of river Hindon. It was observed that dissolved organic carbon (DOC) of river Kali and Krishni is 429.6 and 339.2 mg/L but the values of log KOW and SUVA are less in river Kali and Krishni. Values of log KOW and SUVA was represented the nature of river Kali, and Krishni is hydrophilic. Organic compounds are also identified individually by gas chromatography and mass spectroscopy (GC-MS) and characterized by their reported log KOW values. GC-MS study verified most of the organics present in river Kali and Krishni are hydrophilic in nature.